2015
DOI: 10.1007/s11069-015-1822-7
|View full text |Cite
|
Sign up to set email alerts
|

Seismic site effects observed on sediments and basaltic lavas outcropping in a test site of Catania, Italy

Abstract: Ambient noise measurements and a set of 44 moderate magnitude earthquakes were used to study the role of local geology and morphology on the site response of a small hill in the northern part of Catania, on top of which the University Astronomical Observatory is located. The study area has a gentle topography with a flat surface at the top, and it is characterized by a complex sedimentary sequence lying between a clayey basement and an upper volcanic formation. The recorded data were processed through standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 53 publications
0
15
1
Order By: Relevance
“…The lava flows are the most extended lithotype outcropping in the urban area, covering almost the entire city substratum and deeply changing the original morphology. Borehole data have highlighted the heterogeneous nature of this formation, which is characterized by alternating compact and scoriaceous levels that are extremely variable in thickness [43,44]. Moreover, the presence of pyroclastic levels is observed in the sedimentary sequence of sand and sandy clays.…”
Section: Geologic Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The lava flows are the most extended lithotype outcropping in the urban area, covering almost the entire city substratum and deeply changing the original morphology. Borehole data have highlighted the heterogeneous nature of this formation, which is characterized by alternating compact and scoriaceous levels that are extremely variable in thickness [43,44]. Moreover, the presence of pyroclastic levels is observed in the sedimentary sequence of sand and sandy clays.…”
Section: Geologic Settingmentioning
confidence: 99%
“…It has to be remembered that the presence of lava flows at the surface could imply the existence of possible velocity inversions with the underlying soft sediments, which could give rise to a HVSR amplitude lower than one unit [51][52][53]. Panzera et al [44] tested the influence of lava thickness on the HVSR amplitude, in the frequency range 1.0-10.0 Hz. The authors observed that the amplitude of the spectral ratio peaks decayed, reaching values lower than one, when massive lava with a thickness higher than 20 m overlaid sedimentary terrains.…”
Section: Ambient Vibration Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among these hazards, the most frequent and devastating are landslides which severely affected the only route connecting the province of Gilgit-Baltistan with China (Derbyshire et al 1996;). The frequent land-sliding in the region can be mainly related to the abundance of unconsolidated, highly weathered and fractured geological formations; well-developed rock discontinuities because of the active tectonics, frequent earthquakes, uncontrolled blasting for construction and repair of the roads, presence of the largest glaciers out of the polar regions, precarious locations of alluvial, lacustrine and moraine deposits; severe climatic conditions leading to rapid weathering, poor drainage conditions, scarcity of vegetation, high rates of erosion and anthropogenic activities on unstable slopes (Derbyshire et al 2001;Kamp et al 2008;Panzera et al 2015;Shafique et al 2016).…”
Section: Landslide Along Karakoram Highway (Kkh) Pakistanmentioning
confidence: 99%
“…Etna (stations locations are shown in the inset map of Fig. 7a), the stratigraphic sequence and local velocity model were made by integrating literature information and geological observations (Azzaro et al, 2010;Branca et al, 2011;Branca and Ferrara, 2013;Panzera et al, 2011Panzera et al, , 2015Priolo, 1999). The soil models consist of a number of viscoelastic layers, stacked over a half-space, each of them being defined by the thickness (h), the velocity of the body waves (V p and V s ), the density (ρ) and the Q factor, which controls the inelastic properties.…”
Section: Accounting For Site-specific Responsementioning
confidence: 99%